2021
DOI: 10.1155/2021/6644861
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Based Vehicle Classification in Adverse Illuminous Conditions for Intelligent Transportation Systems

Abstract: In step with rapid advancements in computer vision, vehicle classification demonstrates a considerable potential to reshape intelligent transportation systems. In the last couple of decades, image processing and pattern recognition-based vehicle classification systems have been used to improve the effectiveness of automated highway toll collection and traffic monitoring systems. However, these methods are trained on limited handcrafted features extracted from small datasets, which do not cater the real-time ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The above discussion clearly demonstrates the rise in the usage of cameras and related computer vision algorithms in cars and car safety [25,26]. The groundbreaking development of neural networks during the last decade has also contributed to their application in image processing [27], where one of their most important functions is the detection of specific objects in images [28].…”
Section: St-openunisthrmentioning
confidence: 95%
“…The above discussion clearly demonstrates the rise in the usage of cameras and related computer vision algorithms in cars and car safety [25,26]. The groundbreaking development of neural networks during the last decade has also contributed to their application in image processing [27], where one of their most important functions is the detection of specific objects in images [28].…”
Section: St-openunisthrmentioning
confidence: 95%
“…Butt et al [14] suggested a CNN-related vehicle classification algorithm to improve the strength of vehicle classification in real-time applications. Previously, pre-trained Inception-v3, AlexNet, Visual Geometry Group (VGG), ResNet, and GoogleNet were fine-tuned over self-constructed vehicle datasets so as to evaluate its execution efficiency in terms of convergence and accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…However, the region of interest is usually strongly cropped to remove the background and requires a certain angle image; this strategy, for example, is suited for parking lot cameras. There have been successful experiments to determine the type of vehicle, such as a car, van, truck, or another, with an accuracy of up to 99.68 % using a modified pre-trained ResNet-152 model [3] or 76.28 % using ResNet34 [4]. Another example shows that the AlexNet architecture can be used to produce a perfect classifier to assess the position of a vehicle [16].…”
Section: B Classification Of Vehicle Attributesmentioning
confidence: 99%
“…vehicle is constantly being examined due to the increasing use and research of convolutional neural networks (CNNs) and the development of the graphics processing unit. CNN has already been used to detect and track cars or to count the number of cars passing by on the road [2], [3]. However, due to the most severe CNN constraint of requiring a large dataset, the transfer learning approach [4] was designed to tackle limited data resources.…”
Section: Introductionmentioning
confidence: 99%